RESPON BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) YANG MENGALAMI CEKAMAN GENANGAN AIR TERHADAP PUPUK DAUN DAN GIBERELIN - Reza Kurniawan; Gunawan Tabrani; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research does to increase of palm oil seedling on waterlogging growth with foliar fertilizer and gibberellins application. Research conducted in research farm of Agriculture Faculty, University of Riau, Pekanbaru from September until Desember 2016. This research arranged experimentally by using Completely Randomized Design Factorial with 3 replication. Factor I is concentrate of foliar fertilizer  (D) consist of d0 = no foliar fertilizer (0 ppm), d1 = foliar fertilizer 1,500 ppm, d2 = foliar fertilizer 3,000 ppm and factor II is concentrate of gibberellins (G) consist of g0 = no gibberellins (0 ppm), g1 = gibberellins 5,000 ppm, g2 = gibberellins 10,000 ppm. The observed does: height of seedling, amount of leaf midrib, diameter of tubercle, amount of adventif root, volume of root, shoot root ratio and quality index of seedling. The data were analyzed using analysis of variance and followed by Orthogonal at level of 5%. The result showed that interaction of foliar fertilizer and gibberellin only occured at inisiation of adventif root. The foliar fertilizer influent to establishment of adventif root and shoot root ratio, while gibberellins influent to height of seedling and establishment of adventif root. Quality Index of seedling in this research fulfill requirement criteria of palm oil seedling growth. Keywords: palm oil seedling, waterlooging stress, foliar fertilizer and gibberellin